Philology in the Making : Analog/Digital Cultures of Scholarly Writing and Reading. - Kelemen, Pál (Digital Humanities., 2019)
Philological practices have served to secure and transmit textual sources for centuries. However - this volume contends -, it is only in the light of the current radical media change labeled 'digital turn' that the material and technological prerequisites of the theory and practice of philology become fully visible. The seventeen studies by scholars from the universities of Budapest and Cologne assembled here investigate these recent transformations of our techniques of writing and reading by critically examining core approaches to the history and epistemology of the humanities. Thus, a broad praxeological overview of basic cultural techniques of collective memory is unfolded.